Informed Consent in Dental Services: A Perspective on Medical Law in Indonesia - Suleman, Faraliza Zakia; Cherawaty Thalib, Mutia; Aprilia Kaluku, Julisa (Estudiante Law Journal, 2024)
Informed consent is a crucial component of dental services, designed to protect patient rights and minimize legal risks for dentists. In Indonesia, despite regulations being established through various laws, the implementation of informed consent faces several challenges, including low patient literacy, inconsistent information practices, and gaps in regulation and supervision. This study employs a normative approach, analyzing relevant regulations, examining case studies of legal disputes, and reviewing pertinent literature. It also explores the practices of informed consent in developed countries such as the United States and Australia to identify strategies that can be adapted to the Indonesian context. Additionally, the research investigates cultural, technological, and literacy-related barriers that impact the implementation of informed consent. The study's findings reveal that, although regulations regarding informed consent are in place, their practical application remains inadequate. Major obstacles include the absence of specific guidelines for dentistry, limited legal awareness among dentists, and a paternalistic cultural mindset. Furthermore, inadequate documentation of informed consent often creates loopholes that can lead to legal disputes. Based on these findings, the study recommends strengthening existing regulations, developing national guidelines tailored to the dental profession, providing legal training for dentists, and enhancing public health education. It also proposes the use of technology, such as digital applications, to support more effective documentation and information dissemination. These improvements aim to ensure that the practice of informed consent in Indonesian dentistry meets legal, ethical, and patient-centered standards comprehensively